(untitled) (Nexus International Journal of Science and Education, 2024)
This qualitative inquiry aimed to unravel the multifaceted aspects of leadership and management practices impacting classroom dynamics, teacher motivation, and student achievement. The study focused on fourteen (14) high school teachers from Crossing Bayabas National High School, delving into their adaptive leadership practices, management strategies for classroom dynamics, professional development's influence on leadership, and the direct correlation between leadership and student outcomes. Thematic analysis illuminated the coping mechanisms employed by teachers, emphasizing resource utilization, adaptation, impact, and teacher well-being when faced with challenges related to implementing leadership and management practices. Insights from teachers' encounters with these practices highlighted the evolution of pedagogical perspectives, enhanced reflective teaching, and the cultivation of collaborative learning environments. Implementing these insights entails tailored professional development programs for teachers, fostering reflective practices through mentorship, and redesigning classroom setups to promote collaboration. By incorporating these implications into its educational management practices, Crossing Bayabas National High School could create a more dynamic and engaging learning environment, ultimately enhancing student learning experiences and outcomes. These findings hold immense implications for education stakeholders, including the Department of Education, school principals, elementary teachers, students, parents, and future researchers.